Nanofluids for Heat Transfer: Advances in Thermo-Physical Properties, Theoretical Insights, and Engineering Applications - Ashan Induranga; Chanaka Galpaya; Vimukthi Vithanage; Amalka Indupama; Kaveendra Maduwantha; Niroshan Gunawardana; Dasith Wijesekara; Prasad Amarasinghe; Helitha Nilmalgoda; Kasundi Gunasena; Hasith Perera; Shen Hosan; et al. (Energies)
Nanofluids, fluids with different suspended nanoparticles, have shown improved thermo-physical properties in recent research outputs, and they have emerged as promising alternatives for the industrial fluids used in numerous heat exchange applications. Much research has been conducted around the world to develop heat transfer fluids with optimum thermo-physical properties with the help of nanotechnology, especially in the 21st century. Following the latest research outcomes, nanofluids with base fluids of industrially used coolants, such as water, engine oil, transformer oil, electronic coolants, etc., have shown imposing thermo-physical properties compared to their base fluid. Identifying the nanofluids with high performances and lesser practical obstacles to be used as heat transfer fluids is vital. This paper reviews the thermo-physical property improvements of nanofluid properties, such as thermal conductivity, viscosity, density, specific heat capacity, and flash point, along with their theoretical models. Recent studies on using surfactants to improve the stability of nanofluids are also included in this review. The next part of the study reviews the latest research outputs on the thermo-physical properties of nanofluids in applications in engineering disciplines. Later, research on molecular dynamics simulations of nanofluids are discussed. As the final section, this paper presents Nanofluid research related to neural network modeling. Cumulatively, this paper presents a comprehensive review of recent nanofluids research, along with theoretical developments. This review is a cumulative study of the recent studies of nanofluid research in different disciplines. Most of the recent reviews focused on specific applications of nanofluids and do not cover the field from the basics of the nanofluids to their applications. However, this review covers all the aspects of the nanofluid field, along with several important engineering applications.